MOTOR INDUKSI SEBAGAI GENERATOR (MISG) - Adyson Utina (Universitas Halu Oleo, 2008)
The Induce Motor as Generator (MISG) is induction motor operated by generator. MISG are a lot of applied in The Power Plant of Micro hydro (PLTMh). This Research Target is to control potentials voltage used the contactor and ballast load. This controller has simple technology so that it is applied in PLTMh. The Research done by determining characteristic of high voltage output MISG function of load at constant input energy. The Controller design based on it’s characteristic. The Research done in Laboratory of Transmission and Distribution of Majors of Electrotechnic FT-UNHAS. The Result of research shows that manageable output MISG voltage at about from 198 volt to 231 volt. If without controller, so voltage of output MISG about 220 volt to 335 volt. With utilization of voltage Controller also minimize the percentage of unbalance voltage and also frequency reach. Key words: motor,induksi, tegangan, generator